Избранное: сборник / М. И. Цветаева - Цветаева Марина Ивановна (Хрестоматия школьника, 2007)
Экземпляры: (20080116) / Инвентарный номер: 43659 / Цена: 80.41 / Сис.шифр: Р2 / Авт.знак: Ц 26 / ББК: 84(2Рос-Рус)-4